A copula‐based nonstationary frequency analysis for the 2012–2015 drought in California. Issue 7 (31st July 2016) - Kwon, Hyun‐Han; Lall, Upmanu
Abstract: Using a multicentury reconstruction of drought, we investigate how rare the 2012–2015 California drought is. A Bayesian approach to a nonstationary, bivariate probabilistic model, including the estimation of copula parameters is used to assess the time‐varying return period of the current drought. Both the duration and severity of drought exhibit similar multicentury trends. The period from 800 to 1200 A.D. was perhaps more similar to the recent period than the period from 1200 to 1800 A.D. The median return period of the recent drought accounting for both duration and severity, varies from approximately 667–2652 years, if the model parameters from the different time periods are considered. However, we find that the recent California drought is of unprecedented severity, especially given the relatively modest duration of the drought. The return period of the severity of the recent drought given its 4 year duration is estimated to be nearly 21, 000 years. Key Points: A Bayesian approach to a nonstationary, bivariate probabilistic model, including the estimation of copula parameters is developed The return period of the recent drought varies from approximately 667 to 2652 years under nonstationary assumption. The return period of the severity of the recent drought given its 4 year duration is estimated to be nearly 21, 000 years.